Development of Integral Calculus Teaching Materials to Improve Mathematical Reasoning Ability of Mathematics Education Students at HKBP Nommensen Pematangsiantar University - Eva Pratiwi Pane; Ropinus Sidabutar; Golda Novatrasio Sauduran; Theresia Monika Siahaan (research, training and philanthropy institution Natural Aceh, 2023)
Integral is one of the main subjects in the school mathematics curriculum and is the compulsory subject in the Mathematics Education Study Program at HKBP Nommensen Pematangsiantar University, namely the Integral calculus course. Therefore the status of this material is the subject matter for SMA/MK students and students in mathematics education study programs. This study aims to discover how to develop integral calculus to improve the mathematical reasoning abilities of mathematics education students at HKBP Nommensen Pematangsiantar University. Research on the development of integral calculus teaching materials uses the analysis, design, development, implementation, and evaluation stages. Initial and limited field trials were conducted at the Teaching and Education Faculty (FKIP) HKBP University Nommensen Pematangsiantar. The normality analysis of gain (n-gain) in the experimental student class has increased with an average n-gain value of 0.87. Feasibility of Integral Calculus Teaching Materials Integral Calculus obtained percentage values from experts and subjects studied as follows: (1) Post-test scores reached an average of 83 compared to pretest average scores of 48, there was a significant increase. This shows an increase in learning outcomes after using the results of the product development of Integral Calculus teaching materials. Acquisition of the development value of Integral Calculus Teaching Materials has a high level of attractiveness based on the assessment of material/content experts reaching 93.75%; (2) The acquisition of the value of developing Integral Calculus has a high level of attractiveness based on the assessment of design experts getting 86.53%. Also, the importance of developing Integral Calculus has a high level of beauty based on field test assessments reaching 91%.